2001
DOI: 10.1182/blood.v98.3.505
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and expansion of cytomegalovirus-specific cytotoxic T lymphocytes to clinical scale from a single blood draw using dendritic cells and HLA-tetramers

Abstract: Cytomegalovirus (CMV) reactivation in immunocompromised recipients of allogeneic stem cell transplantation is a cause of morbidity and mortality from viral pneumonitis. Antiviral drugs given to reactivating patients have reduced the mortality from CMV but have toxic side effects and do not always prevent late CMV disease. Cellular immunotherapy to prevent CMV disease is less toxic and could provide prolonged protection. However, a practical approach to generating sufficient quantities of CMV-specific cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(80 citation statements)
references
References 33 publications
2
76
0
2
Order By: Relevance
“…CTL represent a key end point in many protocols which currently employ irradiated DC as APC, both in vitro and in vivo (Gong et al, 1997;Celluzzi and Falo, 1998;Fields et al, 1998;Szmania et al, 2001). Using MART-1 presented by HLA-A2 as a model antigen, we have shown that irradiated human DC prime fewer T cells which are less effective at lysing peptide-pulsed targets ( Figure 5).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…CTL represent a key end point in many protocols which currently employ irradiated DC as APC, both in vitro and in vivo (Gong et al, 1997;Celluzzi and Falo, 1998;Fields et al, 1998;Szmania et al, 2001). Using MART-1 presented by HLA-A2 as a model antigen, we have shown that irradiated human DC prime fewer T cells which are less effective at lysing peptide-pulsed targets ( Figure 5).…”
Section: Discussionmentioning
confidence: 94%
“…Both in vitro applications of DC and in vivo immunotherapy strategies can involve treatment of DC with ionising radiation, often to high dose. The rationale for ex vivo DC irradiation is not always clear, but may be designed to prevent continued DC division or the outgrowth of tumour cell components of vaccine preparations (Gong et al, 1997;Celluzzi and Falo, 1998;Szmania et al, 2001). In vivo irradiation of DC may be incidental during clinical radiotherapy, or part of sequencing combined modality treatment with immunotherapy (TeitzTennenbaum et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CMV-infected fibroblasts as APC [6] have generally been replaced either by unseparated PBMC [5] or by defined professional APC populations such as dendritic cells (DC) [9][10][11][12] or activated B cells [13,14]. The CMV antigenic stimulus has been provided by infection of APC with recombinant viral vectors introducing relevant CMV antigens [9,10,13,14], loading with epitope peptides [12] or CMV protein lysates [5,11].…”
Section: Introductionmentioning
confidence: 99%